CHANGES IN BLOOD PRESSURE IN ELDERLY SUBMITED TO RESISTANCE TRAINING - Santos de Castro, Danilo Leandro; Ferreira Moura, Ronaldo; Jesus Siqueira, Gabriel Dutra de; Oliveira Teixeira, Cristina Gomes de (International Journal of Movement Science and Rehabilitation, 2019)
The practice of regular physical activity in improving the quality of life has attracted attention, especially in the increasingly growing elderly population. The aim of the present study was to evaluate the blood pressure improvement of the elderly submitted to resistance training during 12 weeks. A survey was attended by 30 seniors. Weight and height measurement, BMI calculation, perimetry, and systolic and diastolic blood pressure were measured before and after the training session. The results were 12 weeks of resistance training promoted reductions in resting systolic blood pressure values, even when compared to the previous training session (p <0.001). No reductions in pre-training diastolic blood pressure were found (p <0.809). The reduction of cardiovascular pressure after resistance resistively minimize the risk of cardiovascular events. It is concluded that a resistance training practice for an elderly population has many benefits. Resistance training can be used as non-drug therapy in prevention as well as in treatment and systemic arterial hypertension.